Array - Hidayah, Farida Luthfiatul (RETAIN : Journal of Research in English Language Teaching, 2023)
Pronunciation is one of the crucial elements in the language framework that supports proper interaction. However, several researchers have discussed the challenges of teaching and learning pronunciation, especially for ESL learners. Teachers must provide effective learning strategies for students to follow the latest English standards. The goal of this achievement is that students can overcome communication barriers in using the English language. This study aims to determine students’ perceptions of a specific strategy that involves audio-visual media to enhance students’ achievement in pronunciation class. The audio-visual media used in this research is an original English movie with an English caption provided. The subject of this study involved 30 students from grade 9 in a particular junior high school. The research data was taken using a Likert scale questionnaire. The data show positive results on students’ perception of using audio-visual media called "captioned movie" as a learning strategy in pronunciation class. After collecting data, the findings are presented in words as qualitative research. Most respondents claimed that this strategy is joyous and preferable to be applied in pronunciation class since it may decrease their pressure on learning English. Mainly, they pointed out the benefit of implementing this strategy, widening their word knowledge and enriching their vocabulary. Therefore, the researcher argues that providing an authentic subtitled movie to stimulate students’ word recognition is suitable for pronunciation classes. However, the researcher suggests applying these techniques only occasionally because it may reduce learning effectiveness.